Mode of Delivery in Women with Stillbirth: Results of an Area-Based Italian Prospective Cohort Study - Francesca Monari; Daniela Menichini; Cristina Salerno; Valeria Donno; Beatrice Melis; Isabella Neri; Fabio Facchinetti (IMR Press, 2022)
Introduction: The choice of the mode of delivery, in case of stillbirth (SB) (fetus non-viable >22 weeks' gestation), should consider maternal preference, gestational age, bishop score, the clinical condition of the woman, and her previous obstetric history. However, despite these clear indications, data on the effective implementation of the latter are lacking. The aim of our study is to evaluate the different modes of delivery in an Italian population of SBs, according to gestational age, parity, causes of death, obstetric history, and maternal characteristics. Material and Methods: This is an area-based, prospective cohort study conducted in Emilia Romagna, Italy between January 2014 to December 2020. Data included all cases of SB (>22 weeks). Results: From 2014 to 2020, 783 SB occurred out of a total of 232.506 births, with a SB rate of 3.3 per 1000. Labor was spontaneous in 85 (11%). Of remnant, 567 (73.6%) were induced and 118 (15.3%) had no labor. The mode of delivery was vaginal in most of the cases (649/770, 84.3%) and by cesarean section in 121/770 (15.7%) of cases. Emergency CS was most frequent and performed in 89/121 (73.5%) of total CS, representing 11.5% of SB deliveries. Mode of induction did not differ in relation to gestational age at stillbirth, while vaginal delivery was significantly higher in women induced with prostaglandins (p = 0.000) respect to other methods. Nulliparous women had a significantly higher need for multiple methods of induction (p = 0.000) respect multiparous and obese women used more frequently prostaglandins (p = 0.03) than other methods. Women with a history of previous CS presented a significantly higher rate of repeated elective CS (p = 0.000). Moreover, emergency CS was performed more frequent in obese (p = 0.02), diabetic (p = 0.04) and hypertensive (p = 0.04) women and in SB caused by placenta disorders, namely in abruptio placentae (p = 0.000). In the case of chorioamnionitis and funisitis women significantly were induced with prostaglandin (p = 0.000) and delivered vaginally (p = 0.000). Conclusions: The method of induction of labor and the mode of delivery in case of SB did not depend on gestational age at the diagnosis of death, while they are related to placenta disorders representing a relevant condition leading to emergency CS also after diagnosis of fetal death. These data could help obstetric providers in managing the deliveries of stillborn infants.